Penguatan Kesiapsiagaan Bencana Gempabumi di Sekolah Luar Biasa SLB/C Amal Mulia Jakarta Selatan Melalui Poster Rute Evakuasi untuk Siswa Berkebutuhan Khusus - Jeremy Putra Pratama; Ari Yuda Caesar Sutikno; Muhamad Shafar Nur Rahman; M. Syahrul Rezi; Amal Ramadhani Putra; Fathin Aulia Rahman; Abdul Haris Achadi; Imelda Imelda (Lembaga Pengembangan Kinerja Dosen, 2025)
Disaster preparedness in special schools (SLB) is crucial to protect students with special needs. The purpose of this community service is to improve the knowledge and preparedness of SLB/C Amal Mulia Jakarta Selatan students in dealing with earthquake disasters. The method used is a participatory approach involving students, teachers, and school staff in counseling, creating instructional media in the form of evacuation route maps with bright colors, and conducting evacuation simulations. The results showed significant improvements in students' knowledge. On the Earthquake Definition parameter, there was an 800% increase, while the